Synergistic potential of 1α,25-dihydroxyvitamin D3 and calcium–aluminate–chitosan scaffolds with dental pulp cells - Bordini, Ester Alves Ferreira [UNESP] (2019)
Objectives: This study aimed to develop a porous chitosan–calcium–aluminate scaffold (CH-AlCa) in combination with a bioactive dosage of 1α,25-dihydroxyvitamin D3 (1α,25VD), to be used as a bioactive substrate capable to increase the odontogenic potential of human dental pulp cells (HDPCs). Materials and methods: The porous CH-AlCa was developed by the incorporation of an AlCa suspension into a CH solution under vigorous agitation, followed by phase separation at low temperature. Scaffold architecture, porosity, and calcium release were evaluated. Thereafter, the synergistic potential of CH-AlCa and 1 nM 1α,25VD, selected by a dose–response assay, for HDPCs seeded onto the materials was assessed. Results: The CH-AlCa featured an organized and interconnected pore network, with increased porosity in comparison with that of plain chitosan scaffolds (CH). Increased odontoblastic phenotype expression on the human dental pulp cell (HDPC)/CH and HDPC/CH-AlCa constructs in the presence of 1 nM 1α,25VD was detected, since alkaline phosphatase activity, mineralized matrix deposition, dentin sialophosphoprotein/dentin matrix acidic phosphoprotein 1 mRNA expression, and cell migration were overstimulated. This drug featured a synergistic effect with CH-AlCa, since the highest values of cell migration and odontoblastic markers expression were observed in this experimental condition. Conclusions: The experimental CH-AlCa scaffold increases the chemotaxis and regenerative potential of HDPCs, and the addition of low-dosage 1α,25VD to this scaffold enhances the potential of these cells to express an odontoblastic phenotype. Clinical relevance: Chitosan scaffolds enriched with calcium–aluminate in association with low dosages of 1α,25-dihydroxyvitamin D3 provide a highly bioactive microenvironment for dental pulp cells prone to dentin regeneration, thus providing potential as a cell-free tissue engineering system for direct pulp capping.